Echinus-like Cu–Mo2C/C yolk-shell composites for ultrasensitive detection of hydrogen peroxide. (20th March 2021) - Li, Bo; Liu, Li-Hong; Zhang, Xian-Fa; Gao, Yuan; Deng, Zhao-Peng; Huo, Li-Hua; Gao, Shan
Highlights: Echinus-like Cu–Mo2 C/C yolk-shell architecture is simply prepared by in-siu pyrolysis of bimetal-MOFs. Non-enzymatic Cu–Mo2 C/C/GCE sensor for highly efficient detection of H2 O2 is firstly fabricated. This sensor has higher sensitivity and lower detection limit to nM-level H2 O2 . The sensor exhibits a good practicality for the detection of H2 O2 in spiked human serum. Abstract: Nanomolar electrochemical detection of hydrogen peroxide has been recently looking forward owing to its extensive applications. Herein, Cu–Mo2 C/C material was simply prepared by in-situ pyrolysis of new 3-D covalent bimetallic-organic framework [Cu(Mo2 O7 )L]n [L: N-(pyridin-3-ylmethyl)pyridine-2-amine] crystals under N2 /H2 atmosphere, which presented ultrasensitive detection to H2 O2 . The Cu–Mo2 C/C composite displays unique echinus-like yolk-shell structure, and Mo2 C/C nanosheets were also obtained from the above composite after copper removal by liquid phase etching. Subsequently, the two composites were modified to the surface of glassy carbon electrode (GCE) by simple drop-coating, and the non-enzymatic electrochemical sensors were successfully fabricated. Cu–Mo2 C/C/GCE presents prominent electrocatalytic H2 O2 properties with high sensitivity of 392.7 μAmM −1 cm −2 and wide detection range of 0.12 μM~2.57 mM. The limit of detection (LOD) can be as low as 40 nM, which is 3.2 times larger than that of Mo2 C/C/GCE. Such remarkable ultrasensitive H2 O2 performance is mainly ascribed to the unique microstructure of Cu–Mo2 C/C composite, platinum-like Mo2 C, as well as copper and carbon co-doped. In addition, the Cu–Mo2 C/C/GCE sensor has been successfully utilized to the detection of H2 O2 in spiked human serum. The satisfactory results indicate that this electrode material has certain potential applications in the fields of biology and food. Graphic abstract: Image, graphical abstract